Foreign Direct Investment Inflows and Labor Productivity in Pakistan: A Sector-Wise Panel Cointegration Analysis - Serfraz, Ayesha (Asian Journal of Economics and Empirical Research, 2018)
This study empirically analyzes the effects of sector-wise FDI inflows on respective sector-wise labor productivity for a panel of seven major sectors of Pakistan’s economy covering time period of 1997-2016. For empirical analysis, sector-wise FDI inflows has been used as an independent variable while sector-wise labor productivity is a dependent variable. Initial tests conclude that LSDV fixed effects model is the most appropriate test for the data being used for empirical analysis. Further tests confirm the existence of a long-run Cointegration between these two variables. Wald test shows that a uni-directional short-run causality exists, running from sector-wise labor productivity to sector-wise FDI inflows. Pair-wise Granger-Causality test further shows that the effects of FDI inflows are not limited to one sector, rather there is an evidence of spillover effect from one sector to an-other. All empirical tests conclude that sector-wise FDI inflows positively affect sector-wise labor productivity in case of Pakistan.